2007
DOI: 10.3748/wjg.v13.i15.2250
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy for a patient with a giant esophageal fistula

Abstract: We describe our experience of treatment for a giant esophageal malignant fistula, which has not been reported previously. A 36-year-old woman who was diagnosed as having massive esophageal small cell carcinoma with metastases was treated with chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…However, in this case, the aortic prosthetic graft infection had been accompanied with esophagomediastinal fistulas but had not perforated, so the patient recovered after medical treatment and three operations. Although cases of esophagomediastinal fistulas due to esophageal cancer [8], esophageal tuberculosis [9], endoscopic ultrasound-guided fine-needle aspiration [10], or esophageal diverticulum [11] have been reported, as far as we know no cases caused by vascular surgery have ever been reported. It is difficult to confirm how the patient's esophagomediastinal fistulas formed.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this case, the aortic prosthetic graft infection had been accompanied with esophagomediastinal fistulas but had not perforated, so the patient recovered after medical treatment and three operations. Although cases of esophagomediastinal fistulas due to esophageal cancer [8], esophageal tuberculosis [9], endoscopic ultrasound-guided fine-needle aspiration [10], or esophageal diverticulum [11] have been reported, as far as we know no cases caused by vascular surgery have ever been reported. It is difficult to confirm how the patient's esophagomediastinal fistulas formed.…”
Section: Discussionmentioning
confidence: 99%
“…This surgical technique was implemented in 2 patients, in which one case required the same procedure twice due to recurrence. 12 Similarly, Mobashir et al performed a double nonresorbable suture circumferential ligation of the fistula tract to guarantee a successful closure, but his approach was through an incision of 2.5 cm above the superior tracheostomy edge to preserve the stoma integrity. 34 In his cohort, the TEP was effectively closed in 100% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…1). [8][9][10]12, Using the OCEBM, 33 studies had a level of evidence of 4. No discrepancies during quality assessment occurred.…”
Section: Literature Search and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has also been observed in other normal tissue such as esophageal fistula after tumor disappearance. 17 These clinical experiences suggest that RT need not be stopped because of a skin defect. In this study, reduction of skin defect and regeneration of normal skin were observed in all patients.…”
Section: Quality Of Life and Symptomsmentioning
confidence: 99%